Sobre la permeabilidad de las mezclas asfálticas densas (parte I) (2012)
Infiltration of water through the interconnected voids of the asphalt layers produces the loss of the adhesive bond between the aggregate surface and the asphalt binder, initiating deterioration which can result in the destruction of the mat. A first step to face the problems caused by the presence of water in these systems is to quantify the in-place permeability of asphalt mixes used on the surface layers that wear traffic. Based on data on the aggregate gradation and on the permeability and the volumetric composition of existing asphaltic pavement cores, an equation has been developed to estimate the permeability of a dense graded asphalt mix, starting from the percentage of air voids and the gradation of the aggregate that constitute it. The equation can be used by pavement engineers to control the permeability of these mixtures during the design phase as well as during its setting in-place.